Uji Organoleptik Produk Tahu Berdasarkan Suhu dan Lama Penyimpanan Terhadap Mutu Tahu di Kabupaten Kupang - Manoe, Jenica Arnola; Hinga, Indriati A. Tedju; Setyobudi, Agus (Faculty of Public Health, Nusa Cendana University, 2019)
Tofu is one type of food made from the soybean. Protein content and high water content make tofu easily damaged. Solving this problem is needed the right way to be able to maintain the quality of knowing physically, so that can be stored for a long time without experiencing quality changes and can be accepted and safe for consumers. The purpose of this study was to determine the optimal temperature and storage time of tofu to maintain the quality of tofu in according to the quality requirements of knowing in SNI by looking at the physical changes that have been known during the shelf life. This type of study is a descriptive study to determine the organoleptic properties of tofu which include odor, taste, color, and appereance of tofu during the storage period with the help of panelist of three people. Observation data were analyzed descriptively using tables and explained in narrative form. Tofu samples were taken from three factories in Kupang Regency. The results showed that the ideal of tofu storage temperature was at 40C with a storage time of up to 6 days. The seller and factory owner they should pay attention to the storage temperature and sanitation, so that the tofu sold can survive without reducing the value of quality and taste from tofu.